Spectrum Decomposition-Based Orbital Angular Momentum Communication of Acoustic Vortex Beams Using Single-Ring Transceiver Arrays - Guo, Gepu (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2021)
The orbital angular momentum (OAM)-based acoustic vortex (AV) communication has been proven to provide a topological spinning characteristics for data transmission with an improved channel capacity, exhibiting good application prospects in underwater acoustic communications. To improve the accuracy and efficiency of data communication, the spectrum decomposition of OAM modes for OAM-multiplexed AV beams is studied with a simplified structure of single-ring transceiver arrays. The principle of spectrum decomposition for the single-OAM or OAM-multiplexed AV beams is derived based on the phase-coded approach and the orthogonal property of AVs. With the single-ring arrays of 16 transducers and 16 receivers, numerical studies and experimental measurements of eight-OAM-multiplexed AV beams transmitting ASCII codes are conducted. The formation of OAM-multiplexed AV beams is demonstrated by the cross-sectional scanning measurements, and the OAM modes are decoded successfully with a 16-point circular sampling. Compared with the traditional orthogonality-based decoding algorithm, the spectrum decomposition can be realized using a rotational measurement without the multiple premeasurements of single-OAM AV beams. The favorable results demonstrate the feasibility of the spectrum decomposition-based OAM communication for AV beams using a simplified structure of single-ring transceiver arrays, which would facilitate the practical application in underwater communications